2015
DOI: 10.1016/j.physbeh.2014.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-induced suppression of saccharin intake and morphine modulation of Ca2+ channel currents in sensory neurons of OPRM1 A118G mice

Abstract: Several studies have shown that human carriers of the single nucleotide polymorphism of the µ-opioid receptor, OPRM1 A118G, exhibit greater drug and alcohol use, increased sensitivity to pain, and reduced sensitivity to the antinociceptive effects of opiates. In the present study, we employed a ‘humanized’ mouse model containing the wild-type (118AA) or variant (118GG) allele to examine behavior in our model of drug-induced suppression of a natural reward cue and to compare the morphine pharmacological profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The data in the current manuscript demonstrate that ceftriaxone delays acquisition of cocaine-induced suppression in C57BL/6J mice (Figure 2). Published literature of suppression in mice (e.g., Freet et al , 2013, Freet et al , 2014, Freet et al , 2009) demonstrates that saline controls and drug groups start with similar saccharin intake on Trial 1. This makes sense, of course, given that drug (or saline) has yet to be experienced on that trial.…”
Section: Discussionmentioning
confidence: 97%
“…The data in the current manuscript demonstrate that ceftriaxone delays acquisition of cocaine-induced suppression in C57BL/6J mice (Figure 2). Published literature of suppression in mice (e.g., Freet et al , 2013, Freet et al , 2014, Freet et al , 2009) demonstrates that saline controls and drug groups start with similar saccharin intake on Trial 1. This makes sense, of course, given that drug (or saline) has yet to be experienced on that trial.…”
Section: Discussionmentioning
confidence: 97%
“…These mice have been reported to exhibit increased responsiveness to alcohol (Bilbao et al, 2015; Ramchandani et al, 2011), increased nicotine self-administration (Bernardi et al, 2016), and decreased morphine-induced antinociception (Henderson-Redmond et al, 2016; Mahmoud et al, 2011). Likewise, we previously have demonstrated that humanized OPRM1 A118G mice exhibit greater avoidance of a cocaine-paired saccharin cue in an animal model of the devaluation of natural rewards by drugs of abuse (Freet et al, 2015). It is well known that rodents will avoid a lesser reward if it predicts the future availability of a more preferred, intense reward (for review, see Flaherty, 1996) and it has been hypothesized that, with taste-drug pairings (e.g., saccharin and cocaine), avoidance of intake of the lesser saccharin reward cue is, at least in part, due to a decrease in the relative value of the taste cue when compared with the potent drug of abuse that is expected in the near future (Grigson, 2002, 1997; Grigson et al, 2009).…”
Section: Introductionmentioning
confidence: 86%
“…Humanized 118GG mice, then, defend their intake of the sweet cue despite saccharin-heroin pairings and this effect is illuminated by the use of spaced, rather than massed, trials. Given that this pattern of strain difference is not evident with saccharin-cocaine pairings (Freet et al, 2015), reduced avoidance of the heroin-paired saccharin cue by the 118GG mice may be due to an interaction between the opiate and the subjects’ drive for the sweet or, alternatively, to differential downstream sensitivity to the aversive kappa mediated properties of the drug. These alternative hypotheses are addressed.…”
mentioning
confidence: 99%
“…This substitution strategy at this position of exon 1 has been shown to produce a similar reduction in N -glycosylation sites on the mu-opioid receptor protein (Huang et al., 2012). Another method for uncovering the functional role of the A118G polymorphism is to replace the mouse DNA sequence of exon 1 of OPRM1 with the human DNA sequence of exon 1, which creates a chimera protein of the mu-opioid (Mahmoud et al., 2011; Freet et al., 2015). Nonetheless, binge-like eating or feeding responses have not been studied in the “humanized” A118G mouse models, and it is unknown whether there are differences in the humanized A118G mouse model.…”
Section: Discussionmentioning
confidence: 99%